Education correction using years in school or reading grade-level equivalent? Comparing the accuracy of two methods in diagnosing HIV-associated neurocognitive impairment - Rohit, Mona (2007)
Neuropsychological tests generally require adjustments for years of education when determining the presence of neurocognitive impairment. However, evidence indicates that educational quality, as assessed with reading tests, may be a better reflection of educational attainment among African Americans. Thus, African Americans with poor educational quality may be incorrectly classified with neurocognitive impairment based on neuropsychological tests. We compared the accuracy of neuropsychological test scores standardized using reading grade-equivalent versus years of education in predicting neurocognitive impairment among a sample of Whites and African-American adults who were HIV+. Participants were examined by a neurologist and classified with or without HIV-associated neurocognitive disorders according to accepted criteria. Participants were also classified as impaired versus not impaired based on their neuropsychological test scores standardized by 1) self-reported education or 2) WRAT-3 reading grade-level. Cross tabulation tables were used to determine agreement of the two methods in detecting impairment. Among African-Americans, standardized scores derived from reading scores had greater specificity than those derived from years of education (84.1% vs. 77.3). Among the Whites, correction based on years of education had both greater specificity and sensitivity. The results suggest that reading tests may be a useful alternative for determining NCI among African Americans.